Associations of rs1883832 and rs4810485 polymorphisms of CD40 gene with myocardial infarction in the Tunisian population. (18th August 2019) - Soussi, Meriem; Kallel, Amani; Ben Wafi, Safa; Ben Halima, Meriam; Sanhaji, Haifa; Mourali, Mohamed Sami; Jemaa, Riadh; Feki, Moncef
Abstract: Context: Cluster of differentiation 40 (CD40), and its ligand CD40L, are major co-stimulatory molecules whose interactions are important in both cellular and humoral immunity, and has been suggested to play a role in the pathogenesis of acute coronary syndrome. Objective: The aim of this study was to examine the association of CD40 polymorphisms (-1 C>T (rs1883832) and 945G>T (rs4810485)) and myocardial infarction (MI), and to test the association of CD40 gene haplotypes with MI in Tunisians. Materials and methods: Three hundred and fifty MI patients and 301 apparently healthy controls were included in the study. The polymorphisms of CD40 were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: There were significant differences in the genotype and allele frequencies of CD40 gene -1 C>T (rs1883832) polymorphism between cases and controls. Stratifying according to gender, the association between the TT genotype and MI was statistically significant in males, only. Haplotype analysis revealed that the C-T and T-G haplotypes were associated with an increased risk of MI ( p = 0.012 and p < 0.001, respectively). Conclusions: Our work showed a significant association between the -1 C>T (rs1883832) polymorphism of the CD40 gene and MI in the Tunisians.